Arch of Triumph: A Novel of a Man Without a Country - Erich Maria Remarque (New York Random House Trade Paperbacks, 2014)
It is 1939. Despite a law banning him from performing surgery, Ravic - a German doctor and refugee living in Paris - has been treating some of the city's most elite citizens for two years on the behalf of two less-than-skillful French physicians. Forbidden to return to his own country, and dodging the everyday dangers of jail and deportation, Ravic manages to hang on - all the while searching for the Nazi who tortured him back in Germany. And though he's given up on the possibility of love, life has a curious way of taking a turn for the romantic, even during the worst of times...
Keywords: Classics; Fiction; Historical fiction; War fiction